Keterlibatan Masyarakat dalam Arsitektur Islam: Menavigasi Tantangan dan Merangkul Peluang - Dian Nafiatul Awaliyah (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2024)
This paper explores the role of community engagement in Islamic architecture, driven by the influence of Islamic cultural values and principles. The background highlights the significance of architectural design aligned with Islamic values, as well as the challenges posed by contemporary changes and inadequate recognition of community voices. The central research question guiding this study is: How can community engagement enhance Islamic architecture, reflecting Islamic cultural values while adapting to modern societal needs? The research objective is to investigate the challenges and opportunities of community engagement in Islamic architecture and propose strategies for its enhancement. Qualitative methods, including literature review and analysis, were employed to gather insights from various sources. The findings reveal that community engagement in Islamic architecture plays a pivotal role in maintaining the authenticity of Islamic cultural values. Challenges such as contradictory architectural models and lack of recognition of community figures are counterbalanced by opportunities such as promoting traditional practices, utilizing communal spaces, and involving community leaders. These findings emphasize the dynamic nature of Islamic architecture and its ability to adapt while preserving its rich heritage. The paper concludes that community engagement should remain central to Islamic architectural practices, ensuring that they continue to reflect the essence of Islamic societies amidst changing circumstances.